PENYELESAIAN SENGKETA PERMOHONAN PENERBITAN SERTIPIKAT HAK ATAS TANAH DI KOTA BINJAI (Studi Putusan Mahkamah Agung Nomor 175/K/TUN/2012) - ENI NOVIDA SARI CIBRO (PREMISE LAW JURNAL, 2016)
Land registration is aimed to ensure legal certainty. If land is not registered, there will be no legal certainty so that other people will easily claim that it belongs to them. The settlement of dispute in land certificate at Binjai according to the Ruling of the Supreme Court No. 175/K/TUN/2012 is related to the problem of land registration on old rights so that it takes a long process, to the legal force of legal base on land which has not had BPN (National Land Agency) Certificate, and to the legal ground for the consideration of Panel of Judges and its legal consequence of the Ruling of the Supreme Court No. 175/K/TUN/2012. The legal force for written evidence as legal basis on land which has not had BPN Certificate is weaker than that which has BPN Certificate. The consideration of the Panel of Judges on the Ruling of the Supreme Court No. 175/K/TUN/2012 is based on the control of land as a dispute object which is continuously occupied by the petitioner who has gotten the land from his parents. The legal consequence of giving legality of ownership has motivated him to continue requesting for registering disputed land. Legal basis on the old land and the other evidence should be increased to become BPN Certificate for the sake of law in order to guarantee legal certainty and legal protection. It is also recommended that court judges consider the violation against the principles of transparency, speed, and service facility and petitioner once again request for his land registration to BPN of Binjai Keywords: Settlement of Land Dispute, Requesting for Certificate, BPN of Binjai, Binjai City Administration